FINDING OUT THE EXTENT TO WHICH SCIENCE TEACHERS FOR THE FIRST INTERMEDIATE GRADE, PART TWO, ADHERE TO THE RULES OF BUILDING OBJECTIVE QUESTIONS (American Journal of Pedagogical and Educational Research, 2023)
And why any educational system in any era is without a form of evaluation, as the Chinese knew the written exams and they were of a great degree of difficulty in order to choose the excellent category that was entrusted with high-ranking jobs, and the written exams were also used in Greece (Nassar, 2010, 38). ) and with The beginning of the twentieth century, the movement of tests began at the hands of Thorndike, methods of building tests developed, and objective tests appeared. (Abdul Salam et al. 1992, 18)